If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 625 = 25g + -105 Reorder the terms: 625 = -105 + 25g Solving 625 = -105 + 25g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-25g' to each side of the equation. 625 + -25g = -105 + 25g + -25g Combine like terms: 25g + -25g = 0 625 + -25g = -105 + 0 625 + -25g = -105 Add '-625' to each side of the equation. 625 + -625 + -25g = -105 + -625 Combine like terms: 625 + -625 = 0 0 + -25g = -105 + -625 -25g = -105 + -625 Combine like terms: -105 + -625 = -730 -25g = -730 Divide each side by '-25'. g = 29.2 Simplifying g = 29.2
| -3=-2/3(x+2) | | (p^2-16)(p^2-3p-4)=0 | | 6m^2-18m-16= | | 9-4m=3 | | 155x=(120)(155)+120x | | 3x=7x+30 | | 5c-4-2c+1=10c+2 | | 145x=(120)(145)+120x | | 10-8z=2(5-4z) | | X+19=120 | | 7(x+7)-34= | | 150x=(125)(150)+125x | | 5t+8r=11 | | 145x=(125)(145)+125x | | 2x^2-9+1=0 | | 35-16t^2=6 | | -8x+2=3+10-30x | | 7+8(7+4)+9= | | 35-16t^2=35 | | -2.4x=-36 | | 35-16t^2=18 | | -2.4=-36 | | 4(-6x+3)=3(-10+2x) | | c*(x)-(x^2+10*x-4)=0 | | 155x=(115)(155)+115x | | 5*x*x+14*x+m=0 | | 150x=(115)(150)+115x | | 6+-4=5t+8 | | m+2m=-12+2m | | 8(-4)+4y=20 | | 14-16t^2=14 | | h(3a)=x^4+9x^2-8 |